Serp-2, a virus-derived apoptosis and inflammasome inhibitor, attenuates liver ischemia-reperfusion injury in mice - Jordan R. Yaron; Hao Chen; Sriram Ambadapadi; Liqiang Zhang; Amanda M. Tafoya; Barbara H. Munk; Dara N. Wakefield; Jorge Fuentes; Bruno J. Marques; Krishna Harripersaud; Mee Yong Bartee; Jennifer A. Davids; et al. (BMC, 2019)
Abstract Background Ischemia-reperfusion injury (IRI) is an antigen-independent, innate immune response to arterial occlusion and ischemia with subsequent paradoxical exacerbation after reperfusion. IRI remains a critical problem after vessel occlusion and infarction or during harvest and surgery in transplants. After transplant, liver IRI (LIRI) contributes to increased acute and chronic rejection and graft loss. Tissue loss during LIRI has been attributed to local macrophage activation and invasion with excessive inflammation together with hepatocyte apoptosis and necrosis. Inflammatory and apoptotic signaling are key targets for reducing post-ischemic liver injury. Myxomavirus is a rabbit-specific leporipoxvirus that encodes a suite of immune suppressing proteins, often with extensive function in other mammalian species. Serp-2 is a cross-class serine protease inhibitor (serpin) which inhibits the inflammasome effector protease caspase-1 as well as the apoptotic proteases granzyme B and caspases 8 and 10. In prior work, Serp-2 reduced inflammatory cell invasion after angioplasty injury and after aortic transplantation in rodents. In this report, we explore the potential for therapeutic treatment with Serp-2 in a mouse model of LIRI. Methods Wildtype (C57BL/6 J) mice were subjected to warm, partial (70%) hepatic ischemia for 90 min followed by treatment with saline or Serp-2 or M-T7, 100 ng/g/day given by intraperitoneal injection on alternate days for 5 days. M-T7 is a Myxomavirus-derived inhibitor of chemokine-GAG interactions and was used in this study for comparative analysis of an unrelated viral protein with an alternative immunomodulating mechanism of action. Survival, serum ALT levels and histopathology were assessed 24 h and 10 days post-LIRI. Results Serp-2 treatment significantly improved survival to 85.7% percent versus saline-treated wildtype mice (p = 0.0135), while M-T7 treatment did not significantly improve survival (p = 0.2584). Liver viability was preserved by Serp-2 treatment with a significant reduction in serum ALT levels (p = 0.0343) and infarct scar thickness (p = 0.0016), but with no significant improvement with M-T7 treatment. Suzuki scoring by pathologists blinded with respect to treatment group indicated that Serp-2 significantly reduced hepatocyte necrosis (p = 0.0057) and improved overall pathology score (p = 0.0046) compared to saline. Immunohistochemistry revealed that Serp-2 treatment reduced macrophage infiltration into the infarcted liver tissue (p = 0.0197). Conclusions Treatment with Serp-2, a virus-derived inflammasome and apoptotic pathway inhibitor, improves survival after liver ischemia-reperfusion injury in mouse models. Treatment with a cross-class immune modulator provides a promising new approach designed to reduce ischemia-reperfusion injury, improving survival and reducing chronic transplant damage.